Model Penginjilan Rasul Paulus Dalam Pelayanan Hamba Tuhan Gereja SIB Sabah, Malaysia - Samson Sidi (Sekolah Tinggi Teologi Kanaan Nusantara, 2026)
Evangelism is the theological mandate of the church, originating from the Great Commission and forming the core of Christian ministry throughout history. In the New Testament, particularly through the ministry of the Apostle Paul, evangelism appears as a theological, contextual, and transcultural practice of faith. However, in the context of the contemporary church, the model of evangelism is often reduced to a pragmatic approach that pays little attention to theological depth and social context sensitivity. This phenomenon is evident in the ministry of the ministers of the Sabah Borneo Gospel Church (SIB), who serve in a multi-ethnic, multilingual, and multireligious society with various social and regulatory limitations. This study aims to analyse the evangelism model of the Apostle Paul and relate it to the ministry of the ministers of the SIB Church in Sabah, Malaysia. The research method used is qualitative with a literature study approach through analysis of biblical texts and relevant missiological literature. The results of the study show that the Apostle Paul's model of evangelism is rooted in a Christocentric theological foundation, manifested through relationships, dialogue, and contextual living testimony, and inspired by a cross-centred ethos that interprets suffering as an integral part of faithfulness. This model affirms evangelism as a transformative theological practice, not merely a verbal activity. Its relevance to the ministry of SIB Sabah ministers is evident in its ability to bridge the faithfulness of the Gospel with social sensitivity, interfaith dialogue, and perseverance in ministry in the midst of a pluralistic society.AbstrakPenginjilan merupakan mandat teologis gereja yang bersumber dari Amanat Agung dan menjadi inti identitas pelayanan Kristen sepanjang sejarah. Dalam Perjanjian Baru, khususnya melalui pelayanan Rasul Paulus, penginjilan tampil sebagai praksis iman yang bersifat teologis, kontekstual, dan transkultural. Namun, dalam konteks gereja kontemporer, model penginjilan sering kali mengalami reduksi menjadi pendekatan pragmatis yang kurang memperhatikan kedalaman teologi dan sensitivitas konteks sosial. Fenomena ini terlihat dalam pelayanan hamba Tuhan Gereja Sidang Injil Borneo (SIB) Sabah yang melayani di tengah masyarakat multietnis, multibahasa, dan multireligius dengan berbagai keterbatasan sosial dan regulatif. Penelitian ini bertujuan untuk menganalisis model penginjilan Rasul Paulus dan merelevansikannya bagi pelayanan hamba Tuhan Gereja SIB Sabah, Malaysia. Metode penelitian yang digunakan adalah kualitatif dengan pendekatan studi pustaka melalui analisis teks Alkitab dan literatur teologi misi yang relevan. Hasil penelitian menunjukkan bahwa model penginjilan Rasul Paulus berakar pada landasan teologis yang kristosentris, diwujudkan melalui relasi, dialog, dan kesaksian hidup yang kontekstual, serta dijiwai oleh etos salib yang memaknai penderitaan sebagai bagian integral dari kesetiaan iman. Model ini menegaskan penginjilan sebagai praksis teologis yang transformatif, bukan sekadar aktivitas verbal. Relevansinya bagi pelayanan hamba Tuhan SIB Sabah tampak dalam kemampuannya menjembatani kesetiaan Injil dengan kepekaan sosial, dialog lintas iman, dan ketekunan pelayanan di tengah masyarakat majemuk.